Risk correlates of non-medical use of prescription stimulants among high school students in Iceland - Unnur Elsa Reynisdóttir 1997- (2021)
The aim of the current study was to examine potential risk correlates of non-medical use of prescription stimulants (NMUPS) among high school students in Iceland, as previous studies have mainly focused on college students in the United States and less is known about NMUPS among high school students. Cross-sectional data from a random sample of 2,053 students aged 16-19 years old (51.8% girls) were used, as part of the larger survey Youth in Iceland 2018. The results revealed a lifetime NMUPS prevalence of 5.1%. Students with a history of NMUPS were more likely to be male, have lower grades, report inattention problems interfering with academic performance, more depressive and anxiety symptoms, perceive lower parental monitoring and parental support, and have a history of other substance use compared to students without a history of NMUPS. Binary logistic regression analyses demonstrated that marijuana use in the overall model, parental monitoring and inattention problems among girls, and non-medical use of other prescription drugs among boys and girls significantly predicted NMUPS when accounting for other risk correlates. These findings can assist in identifying high-risk students to help inform prevention and intervention efforts. Longitudinal research is needed to examine directional relationships. Helsta markmið rannsóknarinnar var að skoða mögulega áhættuþætti misnotkunar lyfseðilsskyldra örvandi lyfja meðal framhaldsskólanemenda á Íslandi, þar sem meirihluti rannsókna hefur einblínt á háskólanema í Bandaríkjunum og minna er vitað um misnotkun lyfseðilsskyldra örvandi lyfja meðal framhaldsskólanema. Stuðst var við tilviljunarkennt úrtak 2053 nemenda á aldrinum 16-19 ára (51,8% stelpur) úr rannsókninni Ungt fólk á Íslandi 2018. Niðurstöður rannsóknarinnar gáfu til kynna að 5,1% þátttakenda höfðu misnotað lyfseðilsskyld örvandi lyf á lífsleiðinni. Nemendur sem höfðu sögu um misnotkun voru líklegri til að vera karlkyns, hafa lægri meðaleinkunnir, glíma við athyglisbrest sem hefur áhrif á frammistöðu í námi, ...